Limit the auditor's personal judgment and its reflection on the quality of the audit report - ابراهيم, لبنى زيد; عبد الرحمن, دعاء محمد (Journal of Economics and Administrative Sciences, 2019)
The main objective of the audit is The asset is maintained and operated efficiently and is done through to detect fraud and errors in the financial statements and to verify the accuracy and accuracy of the information contained therein and to give a neutral technical opinion on the basis of that, thus the auditor has a professional responsibility in achieving this goal, and that the effects of issuing a wrong opinion works on The loading of the beneficiaries is significant damage, And therefore the presence of any error or bias of the auditor when taking personal judgments in relation to the determination of the relative importance and the selection of audit samples and determine the adequacy and validity of evidence and implementation of the analytical procedures and audit of the accounting estimates, reflected negatively on the quality of his final report, and for this is limiting the personal judgment of the auditor is necessary from While rationalizing it through international auditing standards, The purpose of the research is to clarify the concept and determinants of the auditor's personal judgments when performing audit work, preparing the report, determining the role of international auditing standards in reducing the auditor's personal judgment, and determining the relationship between the auditor's personal judgment and the quality of his report. The researchers reached a set of conclusions, the most important of which is when the auditor performs his personal provisions, he is committed to implementing the requirements of the international auditing standards at a high rate, which is close to the ideal state of compliance ratio, which helps in reducing the risk of personal judgment of the auditor and reducing them. As a result, the auditors' compliance with the requirements of international auditing standards that limit personal judgments and lead to quality reports in terms of accuracy, objectivity, timeliness and clarity. The research concluded with a set of recommendations, namely: the necessity of researchers' interest in the subject of limiting the auditor's personal judgments and attention to the entrance of the standards of ethical and professional conduct, as well as the international auditing standards as the most important approaches used in reducing personal judgments With training activities related to personal governance and enhancing awareness and confidence in it to enhance the expertise of auditors